Below the parapet wall - beautifully carved miniature towers; Carvings on the parapet wall - sequences from Mahabharata - Krishna's childhood - Brig. Ajai Singh (2021)
[ Image courtesy: Brig A.P. Singh - www.collectingmoments.in ] If you zoom in to see the carvings on the parapet wall, it is a sequence of episodes from Krishna's childhood.